Predictive Microbiology Coupled with Gas (O2/CO2) Transfer in Food/Packaging Systems: How to Develop an Efficient Decision Support Tool for Food Packaging Dimensioning. Issue 1 (January 2015) - Chaix, Estelle; Couvert, Olivier; Guillaume, Carole; Gontard, Nathalie; Guillard, Valerie
Abstract Coupling gas transfer with predictive microbiology is essential to rationally design modified atmosphere packaging (MAP) strategies to ensure and guarantee food safety. Nowadays, these strategies are generally empirically built and over‑sized since packaging material with high barrier properties is often chosen by default even if such a high level of protection is not systematically required. Protection strategies could be improved using rational sizing based on quantitative analysis and mathematical modeling of mass transfer. This paper aims at reviewing the current knowledge available for developing such a tool and the further research needed. First there is a special focus on oxygen (O2) and carbon dioxide (CO2) solubility and diffusivity parameters, which are absolutely indispensable to accurately model mass transfer in MAP systems. Next, the current knowledge of the effect of O2/CO2 on the growth of microorganisms is explored with an emphasis on predictive microbiology. The last part points out the main bottlenecks and further research needed to be carried out in order to develop an efficient MAP modeling tool for food safety coupling O2/CO2 transfer and predictive microbiology.